Ragweed - Avi, 1937-; Floca, Brian (New York : HarperTrophy, 1999)
Ragweed, a young country mouse, leaves his family and travels to the big city, where he finds excitement and danger and sees cats for the first time.
Prequel to: Poppy.
Grade Three Student
Keywords: Mice -- Fiction; Cats -- Fiction